Exploring The Impact Of Social Environment And Health Worker Involvement On Early Marriage In Kawedanan District, Magetan Regency: A Qualitative Study - Rinawati, Putri; Ramadhanintyas, Karina Nur; Widiarini, Retno (Politeknik Kesehatan Kemenkes Mamuju, 2025)
The phenomenon of early marriage among Indonesian teenagers is increasing every year. Preventive efforts to overcome the increase in early marriage need to be carried out by knowing the factors that cause the phenomenon of early marriage. This study is a qualitative study using a phenomenological research type that aims to understand the nature of the phenomenon of adolescent behavior toward early marriage. The technique used is purposive sampling with a total of 10 informants who were married before the age of 19 from 2022 to 2023. Data collection was carried out through source triangulation, namely interviews with 10 parents or guardians of teenagers, two local health workers, and one officer of the Religious Affairs Office. A survey conducted on the 10 informants found several influences that encourage early marriage. Factors that influence early marriage are the knowledge and level of education of teenagers, which make the mindset of teenagers narrow who do not think about the future so that students who graduate from junior high school have already married early; the role of health workers and officers of the Religious Affairs Office in cases of early marriage that are not balanced; the role of parents in supervising and educating teenagers who are still lacking; the level of parental income based on the parents' jobs also has an influence. The majority of teenagers who marry early come from low-income families.